Algorithmic Advantage: How AI Is Reshaping NCAA Recruiting Strategy and Athlete Mobility - Lawrence W Judge; Marshall Magnusen (Journal of Applied Sports Management, 2025)
Artificial Intelligence (AI) is transforming NCAA sports recruiting by offering scalable, data-rich tools that enhance how talent is identified, evaluated, and strategically pursued. Amid the complexities introduced by the transfer portal, name, image, and likeness (NIL) regulations, and rising recruitment costs, AI enables collegiate programs to make faster, more accurate, and financially informed recruiting decisions. Drawing on examples from emerging technologies and real-world institutional practices, the paper highlights the operational benefits of AI, such as efficiency gains, enhanced evaluation accuracy, and expanded reach to under-resourced or geographically remote athletes. At the same time, it critically explores challenges around algorithmic bias, ethical use, and the displacement of human judgment. The article concludes by identifying future imperatives for athletic departments, including staff upskilling, ethical oversight, and the integration of AI as a strategic partner, rather than a substitute, in building competitive and inclusive collegiate sports programs.
Keywords: college athletics; talent identification; NIL; transfer portal; virtual scouting